2000
DOI: 10.1159/000045708
|View full text |Cite
|
Sign up to set email alerts
|

Smoking – A Renal Risk Factor

Abstract: One of the most important tasks of clinical and experimental nephrology is to identify the risk factors of progression of renal failure. A major renal risk factor which has not been sufficiently acknowledged despite increasing evidence is cigarette smoking. Diabetologists were the first to recognize the adverse effects of smoking on the kidney: both in type 1 and in type 2 diabetes smoking (i) increases the risk of development of nephropathy and (ii) nearly doubles the rate of progression to end-stage renal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 92 publications
3
67
0
Order By: Relevance
“…Statistical analysis showed that smoking is associated with significantly elevated risk of DN (OR=2.24, CI 95% 1.27-3.96, P= 0.005) [23], with the greatest risk of CKD development among heavy smokers (>30 pack years) as reflected with OR=2.6 (95% CI=1.53-4.41, p < 0.0001) [23]. These results are in line with earlier clinical studies suggesting smoking as a major exacerbating factor for DN progression in both type 1 [24][25][26] and type 2 diabetics [27,28]. However, this study is suggesting association rather than causation.…”
Section: Smokingsupporting
confidence: 87%
“…Statistical analysis showed that smoking is associated with significantly elevated risk of DN (OR=2.24, CI 95% 1.27-3.96, P= 0.005) [23], with the greatest risk of CKD development among heavy smokers (>30 pack years) as reflected with OR=2.6 (95% CI=1.53-4.41, p < 0.0001) [23]. These results are in line with earlier clinical studies suggesting smoking as a major exacerbating factor for DN progression in both type 1 [24][25][26] and type 2 diabetics [27,28]. However, this study is suggesting association rather than causation.…”
Section: Smokingsupporting
confidence: 87%
“…Several potential mechanisms of smoking-induced renal damage have been discussed (76), but the precise nature of the nephrotoxic effect of smoking is not well understood. The postulated smoking-induced pathomechanisms causing renal damage are summarized in Table 2.…”
Section: Potential Mechanisms Of Smoking-induced Renal Damagementioning
confidence: 99%
“…The nicotine-induced increase in BP and heart rate via sympathetic activation and vasopressin release appears to be a major mechanism contributing to the adverse renal effects of smoking (for review see (76)). Nicotine directly stimulates catecholamine release from peripheral sympathetic nerve endings and the adrenal medulla.…”
Section: Potential Mechanisms Of Smoking-induced Renal Damagementioning
confidence: 99%
“…Large epidemiologic studies had found that smokers are not more frequently hypertensive than nonsmokers (5). These studies, however, did not perform ambulatory BP measurement, which besides that smokers weigh less than their more obese nonsmoking counterparts explains these false-negative results (6). More recent studies using ambulatory BP measurement clearly document that smokers have higher BP than nonsmokers, i.e.…”
mentioning
confidence: 99%